International politics - Schuman, Frederick L. (New York, 1941)
In the thirteenth day of March, 1941, the General Assembly of North Carolina passed a resolution prepared by Mr. Robert Lee By its terms the legislators registered their "profound belief and irrevo cable conviction: That governments are essential to the existence of communities and that the absence of government is anarchy. That there exists an international community, encompassing the entire world, which has no government and which is destined, as a consequence of the present war, either to be ruthlessly dominated and exploited by totalitarianism or to be federated by democracy upon the principle of freedom for all nations and individuals. That all human beings are citizens of this world community, which requires laws and not treaties for its government. That the present conflict is one whose issue involves the survival of free institutions throughout the world, and that it is morally incumbent upon all free peoples, before the war proceeds further, to write the definitive Treaty of Peace in terms of the Constitution of the Federation of the World, in order that those who are called to give their lives and fortunes for the triumph of democracy may have positive knowledge of the incorruptible utility of their sacrifice. . . . Communities without governments perish. Either this community must succumb to anarchy or submit to the restraints of law and order."
Keywords: World politics